Oxyresveratrol and ascorbic acid O/W microemulsion: Preparation, characterization, anti-isomerization and potential application as antibrowning agent on fresh-cut lotus root slices. (1st January 2017) - He, Jianfei; Zhu, Qin; Dong, Xue; Pan, Hongyang; Chen, Jie; Zheng, Zong-Ping
Highlights: OxyME and Oxy + VcME were developed and characterized. ME greatly helped to increase the solubility of Oxy in polar solvent. OxyME and Oxy + VcME were stable in acceleration and long-term storage. Incorporating Vc into OxyME further improved Oxy stability in long-term storage. Oxy + VcME showed strong antibrowning effects on fresh-cut lotus slices in 24 h. Abstract: The purpose of this study is to prepare an oxyresveratrol (Oxy) microemulsion (ME) with improved Oxy's solubility and stability and to investigate its antibrowning effects on fresh-cut lotus root slices. The formula of OxyME consisted of ethyl butyrate, Tween 80, PEG400, and water with w/w of 4%, 10.67%, 5.33%, and 80%, respectively. Encapsulating Oxy into OxyME greatly increased its solubility and stability compared with that of in water. Strong antibrowning effects were observed on fresh-cut lotus root slices treated with OxyME, even better than 4-hexylresorcinol. The addition of ascorbic acid (VC ) into OxyME greatly improved the Oxy stability in long-term storage and antibrowning effects on fresh-cut lotus root slices. However, the simultaneous addition of calcium chloride and VC did not obviously improve the antibrowning effects compared with the addition of VC alone. These results indicated that Oxy + VC ME may be suitable as an antibrowning agent for fresh-cut vegetables.